2023
DOI: 10.1371/journal.pone.0295447
|View full text |Cite|
|
Sign up to set email alerts
|

Pollution halo impact in context of productive capacities, energy poverty, urbanization, and institutional quality

Yuqiang Mo,
Ghulam Rasool Madni

Abstract: The Belt and Road Initiative (BRI) represents a substantial development strategy spearheaded by China. Its central aim is to foster connectivity across a vast geographical area that includes countries spanning Asia, Europe, and Africa. This project played a pivotal role to develop the region on the one side and also raised serious environmental concerns on the other side. There is extensive literature explored the various dimensions affecting the environment in BRI partner countries but there is hardly any stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Practical skills are fundamental in vocational education [ 41 ]. Multimedia technology offers opportunities for hands-on learning through simulations, virtual labs, and interactive tutorials, allowing students to practice and refine skills in a controlled environment [ 23 , 76 ]. Multimedia tools facilitate collaboration among students and instructors.…”
Section: Discussionmentioning
confidence: 99%
“…Practical skills are fundamental in vocational education [ 41 ]. Multimedia technology offers opportunities for hands-on learning through simulations, virtual labs, and interactive tutorials, allowing students to practice and refine skills in a controlled environment [ 23 , 76 ]. Multimedia tools facilitate collaboration among students and instructors.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the study highlight that globalization has significant positive impact on export of cultural products, influencing both the nature of cultural exports and their spatial distribution. Globalization opens up international markets, providing opportunities for cultural products to reach a broader audience [ 51 ]. This leads to increased export potential for various cultural items such as music, films, literature, and art across borders.…”
Section: Discussionmentioning
confidence: 99%
“…By investing in innovation, China has been able to improve the quality and competitiveness of its products, making them more attractive to international markets. This has helped Chinese industries expand their presence globally and compete with other leading economies [37][38][39][40]. It is also found that innovations have a spatial impact across provinces in China, with some regions benefiting more than others.…”
Section: Discussionmentioning
confidence: 99%